Competências em tecnologias digitais na Educação Superior no Brasil e em Portugal - Fernandes, Maria Onilma Moura (2015)
Investigates the constructions of competences in Digital Technologies in Higher Education, hired within developed experiences in universities of Brazil and Portugal, taking as parameters the European reports about Learning and Innovation as a reference of competences building and theorical constructs developed by Le Borted. The Learning and Innovation and Digital Competences were priorized skills in the study for been considerate competences by European union necessary for men and women inclusion in the cultural and social current context of pedagogical projects courses in 09 brazilian universities and 03 portuguese universities were analyzed with the use of Web Qualitative Data Analysis – WebQDA – software support to the analyze of the qualitative data not numeric and under structured that allowed data agglutination in numerical and triangulated matrices with descriptive speeches. The data were introduced by the utilization of documentary analyze techniques and content of analyze with the purpose to identify the concept of skills in literature and presence of the required competences in graduated. The result of the research pointed to the integration, combination and mobilization from the responsible resources, according to Le Boterd skills constructions in Brazil and also in Portugal. This result can be testified by the incipience in identification of Learning and Innovation, Digital Competences in the required skills of the graduated that was formulated on the refered PPC.